2021
DOI: 10.1093/mnras/stab003
|View full text |Cite
|
Sign up to set email alerts
|

The COMBS Survey - II. Distinguishing the metal-poor bulge from the halo interlopers

Abstract: The metal-poor stars in the bulge are important relics of the Milky Way’s formation history, as simulations predict that they are some of the oldest stars in the Galaxy. In order to determine if they are truly ancient stars, we must understand their origins. Currently, it is unclear if the metal-poor stars in the bulge ([Fe/H] < −1 dex) are merely halo interlopers, a unique accreted population, part of the boxy/peanut-shaped bulge, or a classical bulge population. In this work, we use spectra from the V… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 118 publications
1
27
1
Order By: Relevance
“…As the stars in the [Fe/H]-poor tail are slowly rotating, kinematically hot, and [Mg/Fe]-rich, we tentatively associate them with the stellar halo. A contamination by halo stars is further supported by Lucey et al (2021) who, from examining the chemo-kinematics of metal poor bulge stars, found that the fraction of halo interlopers in the bulge increases with decreasing metallicity between −3 < [Fe/H] (dex) < 0.5. In all, our data paints a consistent picture for the origin of the b/p bulge: at least two initial disks with differing dispersions, scale heights, and scale lengths underwent spatial and kinematic fractionation resulting in the b/p bulge of the Milky Way that we observe today.…”
Section: Kinematics Withmentioning
confidence: 76%
“…As the stars in the [Fe/H]-poor tail are slowly rotating, kinematically hot, and [Mg/Fe]-rich, we tentatively associate them with the stellar halo. A contamination by halo stars is further supported by Lucey et al (2021) who, from examining the chemo-kinematics of metal poor bulge stars, found that the fraction of halo interlopers in the bulge increases with decreasing metallicity between −3 < [Fe/H] (dex) < 0.5. In all, our data paints a consistent picture for the origin of the b/p bulge: at least two initial disks with differing dispersions, scale heights, and scale lengths underwent spatial and kinematic fractionation resulting in the b/p bulge of the Milky Way that we observe today.…”
Section: Kinematics Withmentioning
confidence: 76%
“…As the stars in the [Fe/H]-poor tail are slowly rotating, kinematically hot, and [Mg/Fe]-rich, we tentatively associate them with the stellar halo. A contamination by halo stars is further supported by Lucey et al (2021) who, from examining the chemo-kinematics of metal-poor bulge stars, finds that the fraction of halo interlopers in the bulge increases with decreasing metallicity between −3 < [Fe/H] (dex) < 0.5.…”
Section: Kinematics With Metallicity Along the [Fementioning
confidence: 77%
“…However, some stars are potentially simply passing through the inner regions on highly elliptical orbits with large apocentres and are thus not truly inner Galaxy stars. It is still unclear how many of the metal-poor stars currently in the inner Galaxy are halo interlopers, with estimates ranging from 25 to 75 per cent (Howes et al 2015;Kunder et al 2020;Lucey et al 2021). It is desirable to have orbital information of all the stars in PIGS to be able to select a true inner Galaxy sample.…”
Section: Future Workmentioning
confidence: 99%
“…Metal-poor stars are highly outnumbered by metal-rich stars, and dust extinction obstructs and disturbs our view. However, thanks to efficient pre-selection methods and/or large surveys, the number of very metal-poor (VMP) inner Galaxy stars identified and studied has been increasing in recent years (Ness et al 2013;García Pérez et al 2013;Howes et al 2014Howes et al , 2015Howes et al , 2016Casey & Schlaufman 2015;Koch et al 2016;Lamb et al 2017;Lucey et al 2019Lucey et al , 2021Reggiani et al 2020;Arentsen et al 2020b).…”
mentioning
confidence: 99%